Factors associated with hospital length of stay in patients with thoracic hydatid cyst disease undergoing surgical intervention: a retrospective study - Reza Ershadi; Mohammadreza Salehi; Ghazal Roostaei; Niloofar Khoshnam Rad; Sara Soltanmohammadi; Hesam Amini (Journal of Cardiothoracic Surgery)
Abstract Background Hydatid cyst (HC) frequently affects the lungs, making it the second most common site after the liver. This study evaluated the clinical characteristics, surgical procedures, complications, laboratory findings, and factors influencing hospital length of stay (LOS) in patients undergoing surgery for pulmonary hydatid cysts. Methods This retrospective observational study included adult patients who underwent surgery for lung HC between 2017 and 2021. Data were collected using a standardized checklist covering demographics, medical history, clinical symptoms, laboratory findings, treatment details, surgical characteristics, and risk factors. The primary outcome was LOS, defined as the duration between surgery and discharge. Results A retrospective analysis of 214 patients with pulmonary hydatid cysts revealed a male predominance (59.3%; median age, 36 years). The most common symptom was cough (39.3%), followed by chest pain and dyspnea. Right lower lobe involvement (51.4%) and synchronous liver cysts (13.6%) were frequently observed. Elevated erythrocyte sedimentation rate (ESR), eosinophilia, positive serology, prolonged air leak, and fever were correlated with longer LOS. The dominant surgical procedure was cystotomy with capitonnage (95.8%), performed via thoracotomy. Conclusions Most hydatid cysts were located in the right lower lobe, with cough being the most frequent presenting symptom. Thoracotomy and cystotomy with capitonnage were the primary surgical procedures performed. Common postoperative complications included wound infection, empyema, and prolonged air leak. Awareness of factors such as elevated ESR, eosinophilia, positive serology, prolonged air leak, and fever may improve management and reduce hospital LOS.